Functions and Authorities of the Regional Notary Supervisory Council in Improving Notary Service Standards in South Sulawesi - Paikah, Nur (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2023)
This study aims to analyze the function and authority of the Regional Notary Supervisory Board in improving notary service standards in South Sulawesi. This research uses a descriptive analysis method with a qualitative approach through case studies in South Sulawesi. Data were obtained through in-depth interviews with members of the Regional Notary Supervisory Board, notaries, and other related parties. The results of this study indicate that the Regional Notary Supervisory Board has an important role in supervising and improving notary service standards in the region. The value of local wisdom of Bugis Sipakatau, sipakalebbi, and sipakainge is the underlying spirit as well as the novelty of this research. The authorities possessed by the Regional Notary Supervisory Board, such as making ethical guidelines, supervising the behavior of notaries, and enforcing discipline, significantly contribute to increasing the integrity and professionalism of notaries in South Sulawesi. The study found that the board has important roles, like creating ethical guidelines, monitoring notary behavior, and enforcing discipline. It also identified challenges in carrying out these duties. Overall, the research helps us understand how the Regional Notary Supervisory Board enhances notary services in South Sulawesi. Nonetheless, challenges in the implementation of duties and authorities were also identified in this study.